Ferramentas de pesquisa etnometodológicas para alcançar a realidade do público discente - Bonfim, Rodrigo Oliveira (2021)
This article aims to expose the advantages of applying ethnomethodology as a research tool in a micro social environment. The advantages that are presented as a way to assess the characteristics belonging to a social fact present in a micro situation. Tools that are accurate by reach the symbolic interactions produced in the field of studies, in this case the school. An alternative to the peremptory methods provided by positivist sociology and also as a form of social construction of reality for the researcher.